Religiosity and leisure restrictions - Andrade, Rubian Diego (2024)
The association between religiosity and leisure is not always clear, given the different views historically proclaimed in this context, which can interfere with the real meaning of leisure in a given culture. Thus, this cross-sectional, quantitative study aimed to analyze the possible associations between the perception of religion as a restrictive aspect in leisure involvement and sociodemographic and subjective variables. The sample consisted of 992 industrial workers from the Greater Florian & oacute;polis-SC region. As a dependent variable, a question related to the religion and leisure construct of the Brazilian version of the Leisure Constraints Scale (LCS) instrument was used. For most subjects (65.4%), religion can be a restrictive factor to new leisure practices. Furthermore, through inferential statistics, it was identified that education and income were associated with the outcome in workers.